Convert following infix expression to the prefix expression.
a - b + c * (d / e - (f + g))
Answer Posted / rodel
given-> a - b + c * (d / e - (f + g))
note: remember, before we do the infix expression to postfix expression.
We analyze the given data by using the hierarchy of operation (PEMDAS)
In that way, we can do the operation, tracing the hierarchy nos...
sample:
a - b + c * (d / e - (f + g))
5 6 4 2 3 1
pass1: a - b + c * (d / e - (f g +)) infix -> postfix
pass2: a - b + c * (d e / - f g +) infix -> postfix
pass3: a - b + c * (d e / - f g +) infix -> postfix
pass4: a - b + c * (d e / f g + - ) infix -> postfix
pass5: a b - + c d e / f g + - * infix -> postfix
pass6: a b - c + d e / f g + - * infix -> postfix -> Final Answer
Is This Answer Correct ? | 0 Yes | 0 No |
Post New Answer View All Answers
Can we change load factor of hashmap?
Differentiate between queue and stack.
Define leaves?
What are the best data structure courses for gate preparation?
Is sorting a math skill?
What do you mean by selection sort?
What is data and information explain with example?
Define root?
What is the difference between Strings and Arrays?
What are the Advantages and disadvantages of Array?
Define hash function?
What is linked hash set?
Can we increase the size of statically allocated array?
What are the advantages of array?
What is heap tree?